Analisis Pengaruh Ukuran Perusahaan, Variabilitas Persediaan, Variabilitas Harga Pokok Penjualan, Rasio Perputaran Persediaan dan Margin Laba Kotor Terhadap Pemilihan Metode Akuntansi Persediaan (studi pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia) - Tutuk Mahardika; Anik Malikah; Afifudin Afifudin (Universitas Islam Malang, 2017)
Abstract This research aims to know the influence of the size of the company, the variability of inventory, inventory turnover ratio, the variability of cost of goods sold and gross profit margin against the selection of accounting method of inventory. The object of this research is the manufacturing companies listed on the indonesia stock exchange from 2011-2015.The sample of the study consisted of 64 manufacturing company, 54 companies applied the method of average and FIFO methods companies use 10. types of data used in this research is secondary data obtained from historical manufacturing companies through www.idx.co.id. Statistical methods are used to test the hypothesis with the method of logistic regression is enter and significance of 5%.The research results showed that the company's size, variability, inventory, inventory turnover ratio, the variability of cost of goods sold and do not affect the election significantly to inventory accounting method, while the gross profit margin was significantly influential against the selection of accounting method of inventory.Keyword: inventory method, firm size, the variability of inventory, inventory turnover ratio, the variability of cost of goods sold , gross profit margin.